2001
DOI: 10.4269/ajtmh.2001.65.733
|View full text |Cite
|
Sign up to set email alerts
|

Association of NRAMP1 polymorphism with leprosy type but not susceptibility to leprosy per se in west Africans.

Abstract: Abstract. Twin and family studies indicate that host genetic factors influence susceptibility to leprosy and, possibly, leprosy type. Murine studies have suggested a role for the natural resistance-associated macrophage protein 1 (Nramp1) gene, which can influence cellular immune responses to intracellular pathogens. We evaluated a variation in the human homolog, NRAMP1, recently associated with tuberculosis susceptibility in West Africa. A total of 273 patients with leprosy and 201 controls from Mali were gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
1
8

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 24 publications
2
46
1
8
Order By: Relevance
“…[14][15][16][17] Association studies have also demonstrated positive association between this gene and other infectious diseases, for example, leprosy type in the West Africans and human immunodeficiency virus (HIV) infection in Columbians. 18,19 In addition, the SLC11A1 gene also appears associated with autoimmune inflammatory diseases, for example, rheumatoid arthritis (RA) in Canadian Caucasians and Koreans, juvenile rheumatoid arthritis in Latvians, inflammatory bowel disease (IBD) in the Japanese, multiple sclerosis (MS) in South African Caucasians and sarcoidosis in African Americans. [20][21][22][23][24][25] However, some linkage studies failed to demonstrate linkage of the gene to these diseases.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17] Association studies have also demonstrated positive association between this gene and other infectious diseases, for example, leprosy type in the West Africans and human immunodeficiency virus (HIV) infection in Columbians. 18,19 In addition, the SLC11A1 gene also appears associated with autoimmune inflammatory diseases, for example, rheumatoid arthritis (RA) in Canadian Caucasians and Koreans, juvenile rheumatoid arthritis in Latvians, inflammatory bowel disease (IBD) in the Japanese, multiple sclerosis (MS) in South African Caucasians and sarcoidosis in African Americans. [20][21][22][23][24][25] However, some linkage studies failed to demonstrate linkage of the gene to these diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Smaller studies have since found associations between NRAMP1 genotypes and tuberculosis in patients from Japan, Korea and Guinea-Conakry and between NRAMP1 and leprosy type (multibacillary versus paucibacillary) in patients from Mali. [72][73][74][75] It has been found that one of the NRAMP1 polymorphisms, a (GT) n repeat in the 5 0 -untranslated region, influences gene expression, following lipopolysaccharide or IFNg stimulation. 76 Persons who possess the more actively expressed allele have the lowest risk of tuberculosis.…”
mentioning
confidence: 99%
“…Estudos para análise da contribuição do fator genético na manutenção da endemia hansênica em algumas áreas do mundo, têm sido desenvolvidos e a utilização de marcadores genéticos moleculares foram empregados até o momento, não só para determinação da influência do componente genético na hanseníase per se, mas também no padrão de resposta imune do hospedeiro à infecção, bem como o complexo mecanismo de efeitos pleitrópicos dos genes candidatos polimórficos, presentes na população de indivíduos infectados e com doença clínica instalada 12,13,14,15 .…”
Section: Introductionunclassified